Introduction to linear programming as a popular tool in optimal reservoir operation, a review - Heydari M.; Othman F.; Qaderi K.; Noori M.; Parsa A.S. (American-Eurasian Network for Scientific Information, 2023)
Water is a rare and vital natural resource for all biological phenomena and human activities that continuously is needed to be known at any time and place. Taking into the burgeoning growth of population and consequently increasing human needs, the limitation of water resources is a considerable challenge for human. Moreover, asymmetrical distribution of rain time and location in most countries has caused that the water resources management and programming be considered. In order to resolve this problem, researchers are trying to use some techniques in relation with programming and management for a long time. Most of practical and applied problems can be modeled as a linear programming problem regarding all intrinsic complexities. The mentioned reason and also presence of different solving software of linear programming problems have caused that linear programming be used as one of the most practical methods in the field of dam operation for years. In this research, we introduce optimal operation problems of reservoirs by using linear programming techniques and discuss about them. Also, objective and multi objective models were introduced by using some questions. Finally, some popular methods in the field of modeling such problems are introduced. 2015 AENSI Publisher All rights reserved.